2017
DOI: 10.1002/glia.23176
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of a microglial developmental index in mice and in humans reveals a sex difference in maturation and immune reactivity

Abstract: Evidence suggests many neurological disorders emerge when normal neurodevelopmental trajectories are disrupted, i.e. when circuits or cells do not reach their fully mature state. Microglia play a critical role in normal neurodevelopment and are hypothesized to contribute to brain disease. We used whole transcriptome profiling with Next Generation sequencing of purified developing microglia to identify a microglial developmental gene expression program involving thousands of genes whose expression levels change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
264
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(302 citation statements)
references
References 36 publications
17
264
4
Order By: Relevance
“…When specific enrichment was examined for MSigDB immune signatures, DMRs were found to be enriched for gene sets associated with LPS treatment and other types of immune cell activators (Table S3). Furthermore, genes with transcription start sites +/−5kb of DMRs (424 DMRs, total with 209 hyper-methylated DMRs and 215 hypo-methylated DMRs) (Table S5) were significantly enriched for genes responsive to LPS, and other immune stimuli in microglia (Figure 3D) (Hickman et al, 2013; Holtman et al, 2015; Hanamsagar et al, 2017). Together these findings indicate that regions sensitive to MAA methylation differences may contain critical regulatory regions responsive to immune stimuli in microglia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When specific enrichment was examined for MSigDB immune signatures, DMRs were found to be enriched for gene sets associated with LPS treatment and other types of immune cell activators (Table S3). Furthermore, genes with transcription start sites +/−5kb of DMRs (424 DMRs, total with 209 hyper-methylated DMRs and 215 hypo-methylated DMRs) (Table S5) were significantly enriched for genes responsive to LPS, and other immune stimuli in microglia (Figure 3D) (Hickman et al, 2013; Holtman et al, 2015; Hanamsagar et al, 2017). Together these findings indicate that regions sensitive to MAA methylation differences may contain critical regulatory regions responsive to immune stimuli in microglia.…”
Section: Resultsmentioning
confidence: 99%
“…D. Fisher’s Exact Test Odds Ratios for gene list overlap between genes with transcription start sites +/− 5kb from the MAA DMRs. DMR associated genes significantly overlapped genes from the microglial (MG) sensome (Hickman et al, 2013), primed microglia, genes up-regulated acutely in response to LPS (Holtman et al, 2015), and genes up-regulated in microglia two hours after LPS in males and females at postnatal day 60 (P60) (Hanamsagar et al, 2017). See Table S7 for full lists and statistics.…”
Section: Figurementioning
confidence: 99%
“…Notably, MIA with the viral mimic poly I:C can disrupt the pre-microglial developmental stage in offspring and push the microglial transcription state to a more advanced developmental stage [47]. Similarly, we have demonstrated that LPS challenge in late adolescent mice accelerates microglial transcriptional maturation, but only in males [48]. Impacts on microglial transcriptional development likely have significant adverse consequences on neuronal development (e.g.…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 99%
“…so-called “activation”, which remains largely descriptive. We have recently demonstrated a close positive correlation between developmental changes in microglial gene expression and morphology, in mice [48]. Specifically, global transcriptional changes in microglia over normal development correlate strongly with changes in microglial morphology in the same individual.…”
Section: Building Better Models and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation